1996
DOI: 10.1007/bf01886859
|View full text |Cite
|
Sign up to set email alerts
|

Compared chemical properties of dermonecrotic and lethal toxins from spiders of the genusLoxosceles (Araneae)

Abstract: Loxosceles spider venom usually causes a typical dermonecrotic lesion in bitten patients, but it may also cause systemic effects that may be lethal. Gel filtration on Sephadex G-100 of Loxosceles gaucho, L. laeta, or L. intermedia spider venoms resulted in three fractions (A, containing higher molecular mass components. B containing intermediate molecular mass components, and C with lower molecular mass components). The dermonecrotic and lethal activities were detected exclusively in fraction A of all three sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 13 publications
1
12
0
6
Order By: Relevance
“…These authors also showed by SDS-PAGE (15% acrylamide resolution) that the majority of Loxosceles venoms components have molecular mass !8 kDa. These results agree with the results which was published by Barbaro et al (1996b) using gel filtration chromatography. We did not detect these components because they most likely were electrophoresed off the gel due to the lower acrylamide concentration used.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…These authors also showed by SDS-PAGE (15% acrylamide resolution) that the majority of Loxosceles venoms components have molecular mass !8 kDa. These results agree with the results which was published by Barbaro et al (1996b) using gel filtration chromatography. We did not detect these components because they most likely were electrophoresed off the gel due to the lower acrylamide concentration used.…”
Section: Discussionsupporting
confidence: 96%
“…It is interesting to consider that N-terminal sequences of the 32-35 kDa components of L. gaucho, L. laeta and L. intermedia (Barbaro et al, 1996b) as well as L. reclusa and L. deserta (Gomez et al, 2001b) showed high identity, suggesting that they are similar proteins. On the other hand, capillary electrophoresis peptide mapping studies suggest that L. intermedia toxin is more similar to L. laeta toxin than to L. gaucho toxin, indicating that probably some internal amino acid sequence differences exist (Barbaro et al, 1996b) and could reflect on toxicity variations found among Loxosceles venoms (Barbaro et al, 1996a). This variability was also confirmed by Guilherme et al (2001) using monoclonal antibodies that showed the existence of important differences among the epitopes present in the dermonecrotic components of L. gaucho, L. laeta and L. intermedia venoms.…”
Section: Discussionmentioning
confidence: 98%
“…First of all, L. intermedia predominates over L. laeta in terms of abundance and distribution in the urban environment of at least two southern states of Brazil (Fischer, 1994, Mattosinho et al 1997, Andrade et al 2000, which may be partly related to ability differentials in agonistic interactions between the two species as already discussed. Although the venoms of different Loxosceles species have similar dermonecrotic activity, envenomation by L. laeta seems to lead to more severe clinical cases (Barbaro et al 1996a(Barbaro et al , 1996bSezerino et al 1998). For example, in Chile, where L. laeta is predominant, there is a higher prevalence of severe systemic loxoscelism than in southern and southeastern Brazil, where L. intermedia and L. gaucho predominate, respectively (Cardoso et al 1988, Ribeiro et al 1993.…”
Section: Discussionmentioning
confidence: 94%
“…The remainder of the venom composition contains alkaline phosphatase, a variety of proteases, collagenase, esterase, ribonuclease, and deoxyribonuclease. 23,[36][37][38][39] The Nterminal amino acid sequences of the dermonecrotic protein among various Loxosceles species' venom demonstrate identical residue sequences, 40,41 suggesting that the dermonecrotic protein of different Loxosceles species are similar. The contributors of the action of Loxosceles venom are summarized in Figure 4.…”
Section: P a T H O P H Y S I O L O G Ymentioning
confidence: 94%
“…Despite its multivenom specificity, it demonstrates an excellent ability to neutralize the dermonecrotic and lethal activities of L laeta and L intermedia venoms in vivo. 40 A monovalent L intermediaspecific antivenom 124 and a Loxosceles polyvalent (L intermedia, L laeta, and L gaucho) antivenom are also available from the Centro de Produção e Pesquisa em Imunobioló gicos in Paraná, Brazil. The third source of antivenom is produced in Peru at the Institutos Nacionales de Salud in Lima, and the fourth producer is the Instituto Bioclon in Mexico that produces antivenom against Loxosceles and Latrodectus spider venoms.…”
Section: Antivenom Therapymentioning
confidence: 99%